2013
DOI: 10.1021/la4008685
|View full text |Cite
|
Sign up to set email alerts
|

Submicrometer-Sized Pickering Emulsions Stabilized by Silica Nanoparticles with Adsorbed Oleic Acid

Abstract: Oil-water Pickering emulsions of about 200 nm were stabilized by nanosized hydrophilic silica after a simple surface treatment method. We have modified the aqueous silica nanoparticle dispersions by simple adsorption of oleic acid to their surfaces, improving the hydrophobicity of the particles while maintaining their charge and stability. The adsorption was monitored by small-angle X-ray scattering and electrophoretic measurements to estimate the interparticle interactions and surface charges. The effect of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 41 publications
4
68
0
Order By: Relevance
“…At higher liposome concentrations, droplet size levels off. A similar trend has been reported for nanoparticle-stabilized oil/water Pickering emulsions, which form close-packed monolayers 24 . Based on our observed droplet size, liposome size and geometry; liposome coverage at the interface can be estimated.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…At higher liposome concentrations, droplet size levels off. A similar trend has been reported for nanoparticle-stabilized oil/water Pickering emulsions, which form close-packed monolayers 24 . Based on our observed droplet size, liposome size and geometry; liposome coverage at the interface can be estimated.…”
Section: Resultssupporting
confidence: 85%
“…The driving force for particle adsorption (DE) depends on particle radius (R), interfacial tension (g), and contact angle (y), with DE ¼ À pR 2 g(1 À |cos y|) 2 (ref. 24). Although ATPS have low interfacial tensions relative to oil/water systems 12,25 , cells, liposomes and microparticles have been observed at the aqueous/aqueous interface of bulk ATPS [26][27][28][29][30][31][32][33][34][35] .…”
mentioning
confidence: 99%
“…Similar observations were reported by Lv et al, [61] who concluded that SiO 2 nanoparticles can improve the performance of foam in fracturing fluids. Reprinted with permission from Sadeghpour et al [49] Copyright 2013 American Chemical Society.…”
Section: Enhanced/improved Oil Recovery (Eor/ior)mentioning
confidence: 99%
“…1c. It is noteworthy that the TM colloids are only partly masked in Solvent B as they are strictly masked in a solvent containing (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) vol%. However in such a solvent, the incoherent background is important due to the number of H 2 O molecules in the solvent and can hide the ordering peak of the EME internal phase.…”
Section: Contrast Matching Conditions In Neutron Experimentsmentioning
confidence: 99%
“…The Glatter group has recently explored the addition of surfactants to L 2 -nanoparticle mixtures. They used surfactants charged negatively like the TM particles [57]. Despite the electrostatic repulsion between the colloids and the surfactant, the surfactant was found to adsorb onto the surface of the colloids leading to a supercharging, which leads to long-term stability but made the particles even less prone to adsorb onto the L 2 surfaces.…”
Section: Creating a Colloidal Armourmentioning
confidence: 99%